Secular Trends in Hospital Emergency Department Visits for Dental Care in Kansas City, Missouri, 2001–2006 - Hong, Liang (Association of Schools of Public Health, 2011)
OBJECTIVES: We determined the trends, risk factors, and costs of emergency department (ED) visits for dental complaints during a six-year period in Kansas City, Missouri (KCMO). METHODS: We used de-identified hospital discharge data from all facilities serving KCMO during 2001–2006. Using the International Classification of Diseases, Ninth Revision codes, we determined both counts and rates of ED visits related to toothache or tooth injury and analyzed the discharge diagnosis and costs of these visits. We used multivariable regression analysis to assess risk factors for the ED visits for dental complaints. RESULTS: We found a significant increasing trend in dental complaint visits during the six-year period (from 13.1% to 19.0%, p<0.01). Dental caries accounted for 20.4%, pulpitis or periapical abscess accounted for 14.8%, dental injury accounted for 8.7%, temporomandibular joint (TMJ) disorders accounted for 1.5%, and all other unspecified dental diseases accounted for 54.6% of the ED visits for dental complaints. The mean charge was approximately $360 per visit and was highest for TMJ disorders ($747) and lowest for unspecified other dental diseases ($277). Self-pay (38.3%) and Medicaid (32.3%) constituted the majority of the payment sources. Multivariable regression analysis indicated that self-payers, nonwhite people, adults, people with lower family income, and weekends were associated with increased use of ED visits for dental complaints. CONCLUSIONS: There was a significant increasing trend in dental complaint-related ED visits. EDs have become an important site for people with dental problems to seek urgent care, particularly for individuals who self-pay or are on Medicaid.